2018
DOI: 10.17584/rcch.2018v12i1.6631
|View full text |Cite
|
Sign up to set email alerts
|

Effects of indolebutyric acid, stem cutting positions and substrates on the vegetative propagation of <i>Stevia rebaudiana</i> Bertoni

Abstract: Stevia rebaudiana Bertoni es una especie de alta importancia económica debido a la producción de edulcorantes naturales con bajo valor calórico. La producción de semillas de esta especie es irregular y las técnicas de micropropagación aumentan el costo de la producción de plántulas. Por lo tanto, este trabajo tuvo como objetivo optimizar la propagación vegetativa de un genotipo brasileño de esta especie a través de estacas de tallo. El material vegetal se recogió de plantas maduras con 1 año de edad. Se realiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
1
8
0
2
Order By: Relevance
“…Several factors can influence vegetative reproduction success. Types of cuttings, substrates, environment humidity, hormonal balance and stock plants health, physiological conditions, and genetic characteristics are some of the main aspects pointed out as influent for stem cuttings adventitious rooting (ZUFFELLATO-RIBAS and RODRIGUES, 2001;NUNES GOMES and KRINSKI, 2016a;BISCHOFF et al, 2017;PIGATTO et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several factors can influence vegetative reproduction success. Types of cuttings, substrates, environment humidity, hormonal balance and stock plants health, physiological conditions, and genetic characteristics are some of the main aspects pointed out as influent for stem cuttings adventitious rooting (ZUFFELLATO-RIBAS and RODRIGUES, 2001;NUNES GOMES and KRINSKI, 2016a;BISCHOFF et al, 2017;PIGATTO et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The high percent survival of stevia shoot tip stem cuttings regardless of rooting hormones may be due to its meristematic activity, and its hormone production at the apex which induce cell division, cell enlargement that leads to survival and growth. Likewise, these results are best supplied by the studies of [21] which revealed that shoot tip cuttings for the propagation of stevia gave the best results and high percentage survival. Moreover, [11] reported that shoot tip stem cuttings with three nodes, have demonstrated significantly higher values on number of shoots, most number of leaves/branch and high percentage survival.…”
Section: Resultsmentioning
confidence: 96%
“…For Stevia rebaudiana Bert. Stem cuttings, treatment with 2,000 mg L -1 IBA dramatically reduced sprouting percentage, a fact that, according to the authors, was caused because the synthetic auxins in excessive concentrations can have a phytotoxicity effect and inhibit the development of roots and shoots (Pigatto et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In P. serrulata stem cuttings, for example, Fragoso et al (2017) reported that concentrations of 750 and 1,000 mg L -1 IBA promoted longer roots. For stevia propagation, in turn, roots number and length reached maximum values at concentrations of 1,250 and 700 mg L-1 IBA, respectively (PIGATTO et al, 2018).…”
Section: Species/ Treatmentsmentioning
confidence: 96%